How do I trust thee? The employee‐organization relationship, supervisory support, and middle manager trust in the organization - Zhang, Ann Yan; Tsui, Anne S.; Song, Lynda Jiwen; Li, Chaoping; Jia, Liangding (Human Resource Management, 2008)
AbstractGiven the assumption that most employers would like to gain the trust of their employees, what would initiate this trust? This study explores the joint role of the employee‐organization relationship (EOR) and supervisory support in initiating trust among middle managers. The results from a study of 545 middle managers in China show that both EOR and supervisory support are important in creating trust, with supervisory support having a stronger influence than EOR. Further, supervisors play a synergistic role by accentuating the positive influence of the mutual investment EOR approach and attenuating the negative influence of the quasi‐spot contract EOR with the managers. Results reinforce the importance of both formal structure and social processes in cultivating employee trust in the organization. We discuss implications of these findings for future research and human resource management practices. © 2008 Wiley Periodicals, Inc.